2021
DOI: 10.1128/msphere.00321-21
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis Employs a Contact-Dependent Killing System against Competing Enterobacteriaceae

Abstract: The study of bacterial competition systems has received significant attention in recent years. These systems are important in a multitude of polymicrobial environments and collectively shape the composition of complex ecosystems like the mammalian gut.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…mirabilis and/or S. Typhimurium might have killed E. coli by, e.g., microcin secretion (ref reviewed in refs , ). Second, we saw that P.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mirabilis and/or S. Typhimurium might have killed E. coli by, e.g., microcin secretion (ref reviewed in refs , ). Second, we saw that P.…”
Section: Results and Discussionmentioning
confidence: 99%
“…mirabilis isolates were able to kill murine E. coli isolates in coculture in the early stationary phase by using a contact-dependent killing system . The viability assay revealed that P.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to this, lab members can reach her anytime to update her on their newest results, like the exciting hits from a recent transposon screen. Results from this experiment will hopefully shed light on the genetic components of a new competition mechanism of Proteus mirabilis that Judith and her team described last year (Kiani et al, 2021 ). Serendipitously, they discovered the previously unknown ability of P. mirabilis , a commensal in the gut microbiota, to kill E. coli and other species of Enterobacteria .…”
Section: Being Trained and Training The Next Generation Of Scientistsmentioning
confidence: 89%
“…In contrast, Juarez et al (2020) showed that volatile compounds produced by P. mirabilis (including ammonia) negatively affected the growth and biofilm formation of Klebsiella pneumoniae. Moreover, recent work showed that interspecies interactions between P. mirabilis and other Enterobacteriaceae may involve TVISS-independent, as yet unknown contact-dependent mechanisms (Kiani et al, 2021). Importantly, the interactions between P. mirabilis and other bacteria may also result in the acquisition of novel antibiotic resistance mechanisms through horizontal gene transfer (Bonnin et al, 2020).…”
Section: Intra-and Interspecies Interactionsmentioning
confidence: 99%